An unusual case of secondary amenorrhoea. (7th February 2013) - Jain, Deepti
Abstract : A 22-year-old married woman presented with complaints of amenorrhoea and masculinisation. She had hoarseness of voice, hirsutism and ambiguous genitalia. Uterus, cervix and vagina were normal. Investigations revealed a high testosterone level, insignificant luteinizing hormone/follicle stimulating hormone (LH/FSH) and a raised 17-OH progesterone level. Ultrasonography revealed no ovarian or adrenal mass. A diagnosis of 21-hydroxylase deficient classic congenital adrenal hyperplasia, simple virilising form was considered. She was put on prednisolone and given oral contraceptive pill containing cyproterone acetate. Her testosterone level decreased and spontaneous menstruation started. She desired conception and ovulation was induced with clomiphene citrate. She conceived in the second menstrual cycle on clomiphene 50 mg. Imaging at 6 weeks revealed a viable fetus, and an anomaly scan at 16 weeks showed a healthy fetus. However, unfortunately, she aborted around 21 weeks. A scan immediately prior to abortion revealed a subchorionic haematoma.